Preparation method of photocatalyst and application in tetracycline hydrochloride degradation

CN122787006BActive Publication Date: 2026-10-27LULIANG UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611301171.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-08-26
Publication Date
2026-10-27
Estimated Expiration
2046-08-26

AI Technical Summary

Technical Problem

[0014]本发明针对现有技术中生物质利用效率低,功能单一、钛源水解可控性差以及氧空位制备可控性与稳定性极差的缺陷

Benefits of technology

[0059]本发明的优点及其积极效果是:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122787006B_ABST
    Figure CN122787006B_ABST
Patent Text Reader

Abstract

The application belongs to the field of nano photocatalytic material preparation, and particularly discloses a preparation method of a photocatalyst and application of the photocatalyst in tetracycline hydrochloride degradation. The application uses renewable agricultural waste walnut shell as a carbon source, an alkaline source and a prefabricated organic skeleton, realizes in-situ uniform dispersion of walnut shell particles and a titanium source by hydrogen peroxide assisted oxidation-alkali treatment cooperative activation and reverse suspension dispersion technology, avoids agglomeration, constructs a carbon doping and oxygen vacancy cooperative enhancement system, and realizes efficient and selective generation of superoxide free radicals. The material can selectively promote efficient and stable generation of superoxide free radicals, realizes efficient degradation of tetracycline hydrochloride in water under simulated sunlight / visible light driving, and has excellent visible light response ability, catalytic activity and cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of nano-photocatalytic material preparation, and in particular relates to a method for preparing a photocatalyst and its application in the degradation of tetracycline hydrochloride. Background Technology

[0002] Tetracycline antibiotics are among the most widely used broad-spectrum antibiotics globally. Tetracycline hydrochloride, in particular, is widely used in livestock farming and pharmaceuticals due to its low cost and strong antibacterial activity. However, tetracycline hydrochloride is difficult for organisms to completely metabolize; approximately 60%-90% of the parent drug enters the environment through excrement and is widely detected in surface water, groundwater, and even drinking water. Residual tetracycline hydrochloride is difficult to biodegrade and has strong bioaccumulation properties, which not only disrupts the ecological balance of aquatic bodies but also induces the emergence of drug-resistant bacteria and genes. Traditional water antibiotic treatment technologies, such as biochemical treatment, physical adsorption, and chemical oxidation, suffer from low degradation efficiency, easy secondary pollution, insufficient mineralization capacity, and high operating costs, making it difficult to achieve deep purification of tetracycline hydrochloride. Photocatalytic advanced oxidation technology, due to its mild reaction conditions, strong oxidation capacity, and environmental friendliness, is considered one of the most promising technologies for antibiotic pollution control. Its core principle is that when a semiconductor photocatalyst is excited by light, it generates photogenerated electron-hole pairs, which react with dissolved oxygen and water molecules in the water to generate highly active reactive oxygen species (ROS), thereby oxidizing and decomposing antibiotic pollutants into small molecule inorganic substances, achieving harmless treatment.

[0003] Reactive oxygen species include superoxide radicals hydroxyl radicals and singlet oxygen Superoxide radicals play a crucial role in photocatalytic oxidation. Its role is particularly crucial; it can directly participate in the oxidative degradation of pollutants and also serve as a precursor to other reactive oxygen species. In typical photocatalytic systems, It is generated through the single-electron reduction reaction of photogenerated electrons with molecular oxygen, and Hydroxyl radicals are generated through the oxidation of water molecules or hydroxide ions via photogenerated holes. However, the generation of hydroxyl radicals requires the photocatalyst to possess an extremely high valence band potential (2.69 V relative to the standard hydrogen electrode at pH=0), which greatly limits the applicability of most semiconductor photocatalysts. Therefore, promoting the selective reduction of molecular oxygen is crucial for their formation. It has become a highly promising modification strategy in photocatalytic systems.

[0004] Titanium dioxide ( Due to its strong chemical stability, non-toxicity, and low cost, it is currently the most widely used photocatalyst material. However, its commercial application... Anatase has inherent defects that severely limit its practical application in the degradation of tetracycline hydrochloride: First, its large band gap (approximately 3.2 eV for anatase) limits its response to ultraviolet light, which accounts for about 4% of the solar spectrum, resulting in extremely low visible light utilization; second, its rapid photogenerated electron-hole recombination rate leads to low quantum conversion efficiency and insufficient generation of reactive oxygen species; third, anatase... Surface to The activation is weak and cannot be achieved. Its efficient selective generation is difficult to leverage. Its core advantage lies in pollutant degradation.

[0005] To address the aforementioned challenges, current research widely employs strategies such as non-metallic element doping and surface defect engineering to modify the metal. Among them, carbon (C) doping can be achieved... Constructing impurity energy levels within the band gap effectively narrows the band gap and broadens the visible light response range; oxygen vacancies, as typical intrinsic defects, can act as electron traps to suppress carrier recombination and as specific adsorption and activation sites for dissolved oxygen, reducing... The reaction energy barrier for single-electron reduction is significantly increased. The generation efficiency. The two work together to achieve... A significant leap forward in visible light photocatalytic performance.

[0006] However, the controllable construction and long-term stabilization of oxygen vacancies are... This is a core technical challenge that has long remained unresolved in the field of oxygen modification. Current conventional methods for preparing oxygen vacancies all have inherent, unavoidable drawbacks, specifically as follows:

[0007] 1. Physical / Chemical Reduction Method: This is currently the most commonly used method for oxygen vacancy preparation, mainly including high-temperature hydrogen reduction, alkali metal / alkaline earth metal fumigation, and plasma treatment. The core drawback of this method is that it cannot precisely control the concentration, formation location, and spatial distribution of oxygen vacancies, and the generated oxygen vacancies have extremely poor stability, easily being absorbed by atmospheric oxygen. or Oxygen species fill the molecules.

[0008] 2. High-temperature calcination method: This method involves calcining the gas under an inert atmosphere such as nitrogen or argon. High-temperature calcination to remove lattice oxygen is a common method for preparing oxygen vacancies. The core drawback of this method is that, although an inert atmosphere can prevent the refilling of oxygen vacancies to some extent, high temperatures can easily lead to… The severe sintering and agglomeration of nanoparticles leads to a significant decrease in specific surface area and a sharp reduction in the number of surface active sites, which in turn inhibits catalytic performance.

[0009] 3. High-energy irradiation method: This method uses high-energy rays such as electron beams, ion beams, and lasers to irradiate materials, generating point defects through lattice impaction. Although this method can directly and efficiently generate oxygen vacancies, it has a fatal flaw: the irradiation energy is difficult to control precisely, easily producing a large number of undesired defects such as lattice displacements and interstitial atoms, which instead become recombination centers for photogenerated charge carriers, leading to a decline in material performance. Furthermore, it results in high process complexity and production costs, making industrial scale-up difficult.

[0010] 4. Doping-induced method: This method involves introducing heterogeneous elements for doping, utilizing charge imbalance to induce oxygen vacancies, and controlling the defect concentration of titanate materials through ion doping. The core drawback of this method is that the type, valence state, and concentration of the dopant element need to be strictly designed; otherwise, it will not only fail to effectively induce oxygen vacancies but may also inhibit vacancy formation or even become carrier recombination centers.

[0011] In summary, all existing methods for preparing oxygen vacancies face the core challenge of not being able to accurately, controllably, and efficiently generate specific types of uniformly distributed oxygen vacancies. Furthermore, the prepared oxygen vacancies are mostly metastable surface defects, which are easily filled and annihilated by oxygen and hydroxyl groups under service conditions such as water environments and illumination, resulting in extremely poor environmental stability and severely limiting their application. Optimization of the performance of photocatalytic materials and their practical industrial application.

[0012] Existing biomass-based modification technologies also have significant shortcomings: most use chemical reagents such as glucose and glycolic acid as carbon sources, requiring the addition of strong alkalis, chelating agents, and other auxiliary materials to regulate titanium source hydrolysis, resulting in high raw material costs, complex processes, easy introduction of impurities, and poor environmental friendliness; a few technologies that use biomass as a carbon source only treat biomass as a physical loading carrier, failing to explore the hydrophilicity and reactivity of phenolic hydroxyl groups in lignin, and thus failing to simultaneously achieve the full-process synergy of green hydrolysis regulation, in-situ carbon doping, and controllable construction and stabilization of oxygen vacancies. Furthermore, they have not revealed the mechanism by which carbon doping promotes and stabilizes oxygen vacancy generation, and therefore cannot achieve targeted modification. Efficient and stable generation.

[0013] Therefore, it is necessary to develop a method that uses waste biomass as the core raw material, which can simultaneously achieve wide visible light response, high carrier separation efficiency, and controllable stabilization of oxygen vacancies. The efficient and selective generation of TiO2 photocatalysts, along with its green, low-cost, and environmentally friendly preparation method, has significant scientific and industrial application value for the efficient treatment of tetracycline hydrochloride pollution in water bodies. Summary of the Invention

[0014] This invention addresses the shortcomings of existing technologies, such as low biomass utilization efficiency, limited functionality, poor controllability of titanium source hydrolysis, and extremely poor controllability and stability of oxygen vacancy preparation. This invention provides a method for preparing a photocatalyst and its application in the degradation of tetracycline hydrochloride. This method pioneers a full-process synergistic modification mechanism of walnut shells with "one source, multiple functions," revealing the core principle of carbon doping promoting oxygen vacancy generation and atomic-level stabilization, and specifically achieving… The efficient and stable generation of the photocatalyst enables the efficient degradation of tetracycline hydrochloride in water under sunlight / visible light driving, exhibiting excellent visible light response, catalytic activity and cycle stability.

[0015] To solve the above-mentioned technical problems, the technical solution adopted by the present invention is: a method for preparing a photocatalyst, which is carried out according to the following steps:

[0016] Step S1: Pre-treatment of walnut shell raw materials:

[0017] Remove mold, sand and gravel impurities from the walnut shells, ultrasonically clean them with deionized water 3-5 times, 15-20 minutes each time, and then place them in an oven to dry at 60℃ for 12 hours until constant weight. After preliminary crushing, pass them through a 100-mesh standard sieve to obtain coarse walnut shell powder.

[0018] Step S2, High-energy shear flash extraction and activation treatment:

[0019] The coarse walnut shell powder prepared in step S1 was mixed with a 70% volume fraction ethanol aqueous solution and subjected to high-energy shear intermittent flash extraction using a flash extractor at a speed of 15000 rpm. Each treatment lasted 30 seconds, with a 20-second interval, and the process was repeated 3-5 times.

[0020] Step S3, Gentle Activation Treatment:

[0021] The modified walnut shell powder solution was added to sodium hydroxide solution and hydrogen peroxide solution, and reacted gently in a water bath at 60℃ for 4 hours. After the reaction, the solution was filtered, and the filter cake was repeatedly washed with deionized water until the pH of the filtrate was 6.5~7.5 to completely remove free sodium hydroxide. The solution was then vacuum dried at 60-80℃ for 8-12 hours to obtain activated walnut shell powder.

[0022] Step S4, reverse-phase suspension dispersion and hydrolysis reaction:

[0023] 3g of activated walnut shell powder was ultrasonically dispersed in 50mL of aqueous solution. Using reverse-phase suspension technology, 1g of Tween 80 was used as a surfactant, 250mL of toluene was used as the oil phase, and the walnut shell aqueous dispersion was used as the aqueous phase to form a water-in-oil system. After continuous stirring to form a turbid liquid, 1g of tetrabutyl titanate was slowly added dropwise to the system. The titanium source slowly diffused through the oil phase to the surface of the walnut shell particles in the aqueous phase. The in-situ hydrolysis reaction was carried out for 12h under stirring at room temperature.

[0024] Step S5, Precursor Post-processing:

[0025] Centrifuge the reaction product generated in step S4, wash it repeatedly with anhydrous ethanol and deionized water to remove residual solvent and unreacted raw materials, and dry it at 60-80℃ for 10h to obtain the precursor.

[0026] Step S6: In-situ calcination modification under inert atmosphere:

[0027] The precursor was spread evenly in a corundum ark and placed in a tube furnace. Nitrogen gas was introduced at a flow rate of 100-200 mL / min for 30 minutes to completely purge the air from the furnace. Calcination was then performed using a programmed temperature increase of 5 °C / min, maintaining an inert atmosphere throughout the process. After calcination, the mixture was allowed to cool naturally to room temperature under inert gas protection, and then ground to obtain carbon-doped oxygen-rich vacancies. Photocatalyst.

[0028] Furthermore, in step S2, the solid-liquid ratio of the coarse walnut shell powder to the ethanol aqueous solution is 1g:30mL-50mL.

[0029] Furthermore, in step S3, the concentration of the sodium hydroxide solution is 3-5 wt%, and the volume ratio of the walnut shell powder solution to the sodium hydroxide solution is 100 ml: 10-15 ml.

[0030] Preferably, in a method for preparing a photocatalyst, the concentration of the hydrogen peroxide solution in step S3 is 5-8 wt%, and the volume ratio of walnut shell powder solution to hydrogen peroxide is 100 ml: 5-8 mL.

[0031] Preferably, a method for preparing a photocatalyst comprises the following steps:

[0032] Step S1: Pre-treatment of walnut shell raw materials:

[0033] Remove mold, sand and gravel impurities from the walnut shells, ultrasonically clean them three times with deionized water for 15 minutes each time, and then place them in an oven to dry at 60°C for 12 hours until constant weight. After preliminary crushing, pass them through a 100-mesh standard sieve to obtain coarse walnut shell powder.

[0034] Step S2, High-energy shear flash extraction and activation treatment:

[0035] The coarse walnut shell powder prepared in step S1 was mixed with a 70% ethanol aqueous solution at a solid-liquid ratio of 1g:30mL. The mixture was subjected to high-energy shear intermittent flash extraction using a flash extractor at a speed of 15000rpm. Each treatment lasted 30s, with a 20s interval, and the process was repeated 3 times.

[0036] Step S3, Gentle Activation Treatment:

[0037] 100 mL of the flash-extraction modified walnut shell powder solution was added to 15 mL of 3 wt% sodium hydroxide solution and 8 mL of 5 wt% hydrogen peroxide solution, and the mixture was gently reacted in a water bath at 60°C for 4 h. After the reaction was completed, the mixture was filtered, and the filter cake was repeatedly washed with deionized water until the pH of the filtrate was 6.5 to completely remove free sodium hydroxide. The mixture was then vacuum dried at 60°C for 8 h to obtain activated walnut shell powder.

[0038] Step S4, reverse-phase suspension dispersion and hydrolysis reaction:

[0039] 3g of activated walnut shell powder was ultrasonically dispersed in 50mL of aqueous solution. Using reverse-phase suspension technology, 1g of Tween 80 was used as a surfactant, 250mL of toluene was used as the oil phase, and the walnut shell aqueous dispersion was used as the aqueous phase to form a water-in-oil system. After continuous stirring to form a turbid liquid, 1g of tetrabutyl titanate was slowly added dropwise to the system. The titanium source slowly diffused through the oil phase to the surface of the walnut shell particles in the aqueous phase. The in-situ hydrolysis reaction was carried out for 12h under stirring at room temperature.

[0040] Step S5, Precursor Post-processing:

[0041] The reaction product generated in step S4 was centrifuged, washed repeatedly with anhydrous ethanol and deionized water to remove residual solvent and unreacted raw materials, and dried at 60°C for 10 hours to obtain the precursor.

[0042] Step S6: In-situ calcination modification under inert atmosphere:

[0043] The precursor was spread evenly in a corundum ark and placed in a tube furnace. Nitrogen gas was introduced at a flow rate of 100 mL / min for 30 minutes to completely purge the air from the furnace. Calcination was then performed using a programmed temperature increase of 5 °C / min, maintaining an inert atmosphere throughout the process. After calcination, the mixture was allowed to cool naturally to room temperature under inert gas protection and then ground to obtain carbon-doped oxygen-rich vacancies. Photocatalyst.

[0044] Preferably, a method for preparing a photocatalyst comprises the following steps:

[0045] Step S1: Pre-treatment of walnut shell raw materials:

[0046] Remove mold, sand and gravel impurities from the walnut shells, ultrasonically clean them 5 times with deionized water for 20 minutes each time, and then place them in an oven to dry at 60℃ for 12 hours until constant weight. After preliminary crushing, pass them through a 100-mesh standard sieve to obtain coarse walnut shell powder.

[0047] Step S2, High-energy shear flash extraction and activation treatment:

[0048] The coarse walnut shell powder prepared in step S1 was mixed with a 70% ethanol aqueous solution at a solid-liquid ratio of 1g:50mL. The mixture was subjected to high-energy shear intermittent flash extraction using a flash extractor at a speed of 15000rpm. Each treatment lasted 30s, with a 20s interval, and the process was repeated 5 times.

[0049] Step S3, Gentle Activation Treatment:

[0050] 100 mL of the flash-extraction modified walnut shell powder solution was added to 10 mL of 5 wt% sodium hydroxide solution and 5 mL of 8 wt% hydrogen peroxide solution, and the mixture was gently reacted in a water bath at 60℃ for 4 h. After the reaction was completed, the mixture was filtered, and the filter cake was repeatedly washed with deionized water until the pH of the filtrate was 7.5 to completely remove free sodium hydroxide. The mixture was then vacuum dried at 80℃ for 12 h to obtain activated walnut shell powder.

[0051] Step S4, reverse-phase suspension dispersion and hydrolysis reaction:

[0052] 3g of activated walnut shell powder was ultrasonically dispersed in 50mL of aqueous solution. Using reverse-phase suspension technology, 1g of Tween 80 was used as a surfactant, 250mL of toluene was used as the oil phase, and the walnut shell aqueous dispersion was used as the aqueous phase to form a water-in-oil system. After continuous stirring to form a turbid liquid, 1g of tetrabutyl titanate was slowly added dropwise to the system. The titanium source slowly diffused through the oil phase to the surface of the walnut shell particles in the aqueous phase. The in-situ hydrolysis reaction was carried out for 12h under stirring at room temperature.

[0053] Step S5, Precursor Post-processing:

[0054] The reaction product generated in step S4 was centrifuged, washed repeatedly with anhydrous ethanol and deionized water to remove residual solvent and unreacted raw materials, and dried at 80°C for 10 hours to obtain the precursor.

[0055] Step S6: In-situ calcination modification under inert atmosphere:

[0056] The precursor was spread evenly in a corundum ark and placed in a tube furnace. Nitrogen gas was introduced at a flow rate of 200 mL / min for 30 minutes to completely purge the air from the furnace. Calcination was then performed using a programmed temperature increase of 5 °C / min, maintaining an inert atmosphere throughout the process. After calcination, the furnace was allowed to cool naturally to room temperature under inert gas protection and then ground to obtain carbon-doped oxygen-rich vacancies. Photocatalyst.

[0057] Another technical solution to be protected by this invention is: the application of a photocatalyst in the degradation of tetracycline hydrochloride, wherein carbon-doped oxygen-rich vacancies are prepared using the above-mentioned photocatalyst preparation method. Photocatalyst, The photocatalyst was added to the tetracycline hydrochloride solution and stirred in the dark for 25-35 minutes to reach adsorption-desorption equilibrium. Then, the tetracycline hydrochloride was degraded by irradiation with visible light.

[0058] Furthermore, the aforementioned After the photocatalyst has degraded, it is centrifuged and recovered, washed 3-5 times with deionized water and ethanol, and then dried for reuse.

[0059] The advantages and positive effects of this invention are:

[0060] 1. The invention features a groundbreaking "one source, multiple functions" design, which innovatively integrates the four major functions of walnut shell biomass: "natural phenolic hydroxyl slow-release alkali source, in-situ doped carbon source, oxygen vacancy construction promoter and stabilizer, and TiO2 dispersed organic framework." This achieves synergistic effects of a single raw material throughout the entire process, completely avoiding the use of traditional chemical regulators, toxic doping reagents, and flammable and explosive reducing gases. It greatly simplifies the process flow and differs from existing technical solutions that use biomass as a single carbon source, demonstrating a high degree of originality.

[0061] 2. The titanium source hydrolysis process is green and controllable, with sufficient exposure of active sites: Utilizing the slow-release alkalinity of walnut shell phenolic hydroxyl salts, precise and gentle control of the hydrolysis kinetics of tetrabutyl titanate is achieved, fundamentally solving the industry pain point of rapid hydrolysis and aggregation of titanium sources. The prepared TiO2 nanoparticles are uniformly dispersed, have a large specific surface area, and expose more O2 adsorption and activation active sites, providing a more suitable environment for... This provides a structural foundation for efficient generation.

[0062] 3. This invention reveals the core mechanism by which carbon doping promotes and stabilizes oxygen vacancies, through a synergistic positive feedback mechanism of dual modification. High selective generation efficiency. This invention reveals for the first time a triple mechanism of carbon doping: vacancy generation induced by lattice distortion, vacancy stabilization through electronic structure modulation, and synergistic reduction of the carbon layer in situ. This achieves positive feedback synergy between carbon doping and oxygen vacancies, rather than a simple performance superposition; it provides sufficient energy through band structure optimization. The generation of thermodynamic driving force, coupled with the significant reduction of the O2 activation reaction energy barrier through controllable and stable oxygen vacancies, enabled the achievement of... Efficient selective generation.

[0063] 4. This invention completely solves the core pain points of existing oxygen vacancy preparation methods, achieving a leapfrog improvement in vacancy controllability and stability. Through in-situ synchronous doping-defect construction, precise control over the concentration and distribution of oxygen vacancies is achieved, avoiding problems such as crystal structure destruction, particle agglomeration, and the generation of undesirable defects present in existing methods. Atomic-level stabilization of oxygen vacancies is achieved, fundamentally solving the industry problems of easy annihilation and poor environmental stability of oxygen vacancies. During long-term cyclic use, the oxygen vacancy concentration shows no significant decay, and the catalytic performance remains stable. Attached Figure Description

[0064] Figure 1 for Flowchart of photocatalyst preparation.

[0065] Figure 2 For the present invention Band structure of photocatalysts, and the mechanism by which carbon doping promotes and stabilizes oxygen vacancies. A schematic diagram of the reaction mechanism between the formation and degradation of tetracycline hydrochloride. (a) shows the band structure and degradation reaction mechanism, and (b) shows carbon doping and oxygen vacancies (O). V Schematic diagram of the stabilization mechanism.

[0066] Figure 3 The product of Example 1 before and after light exposure The ESR spectrum.

[0067] Figure 4 This is a comparison chart of the degradation rates in the free radical capture experiment of Example 1, verifying... It is the dominant active species in the degradation process.

[0068] Figure 5 The degradation kinetics curves of tetracycline hydrochloride for Example 1 and the comparative product under visible light are shown. Detailed Implementation

[0069] To make the objectives, features, and advantages of the present invention more apparent and understandable, the specific embodiments of the present invention will be described in detail below.

[0070] A method for preparing a photocatalyst, comprising the following steps:

[0071] Step S1: Pre-treatment of walnut shell raw materials: Remove mold, sand and gravel impurities from the walnut shells, ultrasonically clean them with deionized water 3-5 times, 15-20 minutes each time, and then place them in an oven to dry at 60℃ for 12 hours until constant weight. After preliminary crushing, pass them through a 100-mesh standard sieve to obtain coarse walnut shell powder.

[0072] Step S2, High-energy shear flash extraction activation treatment: The walnut shell powder prepared in step S1 is mixed with a 70% ethanol aqueous solution at a solid-liquid ratio of 1g:30-50mL. High-energy shear intermittent flash extraction is performed using a flash extractor at a speed of 15000rpm. Each treatment lasts 30s, with a 20s interval, and the cycle is repeated 3-5 times to fully break the lignin-cellulose cross-linked structure and expose the phenolic hydroxyl functional groups in the lignin.

[0073] Step S3, Mild Activation Treatment: Add 10-15 mL of 3-5 wt% sodium hydroxide solution and 5-8 mL of 5-8 wt% hydrogen peroxide solution to 100 mL of flash-extracted modified walnut shell powder solution and mix. React gently in a 60℃ water bath for 4 hours to achieve mild activation of phenolic hydroxyl groups into salts. After the reaction, filter and repeatedly wash the filter cake with deionized water until the pH of the filtrate is 6.5-7.5 to completely remove free sodium hydroxide. Vacuum dry at 60-80℃ for 8-12 hours to obtain activated walnut shell powder.

[0074] In an alkaline microenvironment, Selective attack on methoxyl groups in lignin ( The demethylation reaction generates new phenolic hydroxyl groups, resulting in a synergistic effect of targeted bond breaking and proton removal, thus significantly increasing the exposure of phenolic hydroxyl groups. The generated phenolic hydroxyl salts significantly increase the solubility of walnut shells in water, which is beneficial for subsequent uniform dispersion, while also providing a weakly alkaline environment for the hydrolysis of tetrabutyl titanate.

[0075] Step S4, Reverse-phase suspension dispersion and hydrolysis reaction: 3g of activated walnut shell powder was ultrasonically dispersed in 50mL of aqueous solution. Reverse-phase suspension technology was used, with 1g of Tween 80 as surfactant, 250mL of toluene as oil phase, and walnut shell aqueous dispersion as aqueous phase to form a water-in-oil system. After continuous stirring to form a turbid liquid, 1g of tetrabutyl titanate was slowly added dropwise to the system. The titanium source slowly diffused through the oil phase to the surface of the walnut shell particles in the aqueous phase. In-situ hydrolysis reaction was carried out for 12h under stirring at room temperature.

[0076] The aqueous phase is separated into micron-sized droplets by the oil phase. Within each droplet, walnut shell particles are uniformly distributed. Tetrabutyl titanate diffuses slowly from the oil phase to the aqueous phase, and the hydrolysis rate is controlled by diffusion, preventing explosive polymerization. The exposed phenolic hydroxyl groups in the walnut shell precisely and gently regulate the hydrolysis and condensation kinetics of tetrabutyl titanate, completely avoiding the rapid hydrolysis, precipitation, and aggregation problems caused by strong alkali. No additional chemical modifiers are required, achieving a green and controllable hydrolysis process. Simultaneously, the generated... The precursor can be anchored in situ onto the organic framework of the walnut shell, achieving nanoscale uniform dispersion and exposing more... Adsorption activates active sites, for The generation provides a structural basis, forming a compact heterogeneous structure.

[0077] Step S5, Precursor Post-processing: Centrifuge the reaction product generated in step S4, wash repeatedly with anhydrous ethanol and deionized water to remove residual solvent and unreacted raw materials, and dry at 60-80℃ for 10h to obtain the precursor.

[0078] Step S6, In-situ Calcination Modification under Inert Atmosphere: The precursor is spread evenly in a corundum boat and placed in a tube furnace. Nitrogen gas is introduced at a flow rate of 100-200 mL / min for 30 minutes to completely purge the air from the furnace. Calcination is then performed using a programmed temperature increase of 5℃ / min, maintaining an inert atmosphere throughout the process. After calcination, the mixture is allowed to cool naturally to room temperature under inert gas protection, then ground to obtain carbon-doped oxygen-rich vacancies. Photocatalyst.

[0079] By in-situ calcination in an inert atmosphere, the controllable generation of carbon lattice doping and stable oxygen vacancies is further achieved, and the carbon doping not only narrows the... The wide bandgap allows for the active promotion of oxygen vacancy generation through lattice distortion and electronic structure modulation, while simultaneously achieving atomic-level stabilization of these vacancies; oxygen vacancies further enhance carrier separation and Activation ability, the two work together to achieve Efficient selective generation.

[0080] This invention protects the products prepared by the above-described method. The nanocomposite photocatalyst is a pure anatase phase, with carbon elements as the main component. Covalent lattice doping Within the crystal lattice, the stability and concentration of oxygen vacancies are controlled, enabling the selective, efficient, and stable generation of superoxide radicals. .

[0081] In this invention, carbon doping not only achieves The modulation of band structure also fundamentally promotes the generation of oxygen vacancies and achieves atomic-level stabilization of oxygen vacancies, completely solving the core pain points of uncontrollable and easily annihilated oxygen vacancies in existing technologies. The core mechanism consists of three points:

[0082] Lattice distortion induces controllable generation of oxygen vacancies: The atomic radius of carbon (0.077 nm) is larger than that of oxygen (0.066 nm), and the electronegativity of carbon (2.55) is significantly lower than that of oxygen (3.44). When carbon atoms substitute for oxygen vacancies... Oxygen atoms in the crystal lattice form When the key is pressed, it will trigger Significant local distortions in the crystal lattice generate lattice stress, leading to changes in the performance of adjacent crystals. Bond lengths elongate and bond energies decrease significantly. During calcination in an inert atmosphere, these weakened bonds... The bonds will break in a directional manner, and the lattice oxygen can be removed in a controlled manner, thereby greatly promoting the generation of oxygen vacancies. The concentration of oxygen vacancies can be precisely controlled by adjusting the amount of carbon doping, thus avoiding the crystal structure damage caused by excessive reduction in existing methods.

[0083] Atomic-level stabilization of oxygen vacancies is achieved through electronic structure manipulation: carbon atom doping is introduced. After lattice formation, the distribution of the electron cloud around the titanium atoms will be altered, causing some... The electrons are reduced to . The existence will break The lattice is electrically neutral, and in order to balance the charge, more oxygen vacancies will spontaneously form in the lattice. This significantly reduces the formation energy of oxygen vacancies and the probability of oxygen vacancies being refilled by oxygen and hydroxyl groups in the environment. This fundamentally solves the core problems of easy annihilation of oxygen vacancies and poor environmental stability in existing technologies, and ensures the stability of the catalytic performance of the material during long-term cyclic use.

[0084] In-situ carbon sources synergistically enhance the reduction effect and prevent particle agglomeration. During the calcination process, the in-situ carbon source generated by the pyrolysis of walnut shells provides a carbon source for lattice doping, avoids sintering and agglomeration during high-temperature calcination, maintains the material's high specific surface area and abundant active sites, and solves the problem that existing high-temperature calcination methods easily lead to particle agglomeration and reduced activity.

[0085] In-situ generation of stable oxygen vacancies, reducing Generation reaction energy barrier: Under high temperature and anaerobic conditions, the incompletely carbonized organic carbon in the walnut shell acts as a reducing agent, reacting with... Selective reduction of surface oxygen atoms in the crystal lattice, combined with the generation of oxygen vacancies induced by carbon doping, leads to... Oxygen vacancies are formed in the crystal lattice with controllable concentration and strong environmental stability. Oxygen vacancies can be used as… The specific adsorption and activation sites of the molecule significantly enhance its adsorption capacity for dissolved oxygen and reduce its concentration. It acts as a reaction energy barrier for single-electron reduction; simultaneously, it can function as an electron trap to rapidly capture photogenerated electrons, significantly suppress the recombination of photogenerated electron-hole pairs, improve the separation and migration efficiency of photogenerated carriers, and further promote... Selective and efficient generation.

[0086] Another technical solution to be protected by this invention is: the application of a photocatalyst in the degradation of tetracycline hydrochloride, wherein carbon-doped oxygen-rich vacancies are prepared using the above-mentioned photocatalyst preparation method. Photocatalyst, The photocatalyst was added to the tetracycline hydrochloride solution and stirred in the dark for 25-35 minutes to reach adsorption-desorption equilibrium. Then, the tetracycline hydrochloride was degraded by irradiation with visible light. After the photocatalyst has degraded, it is centrifuged and recovered, washed 3-5 times with deionized water and ethanol, and then dried for reuse.

[0087] The preparation process and principle of the present invention have been described in detail above. The effectiveness of the method will be verified below through specific embodiments and corresponding performance tests.

[0088] Example 1

[0089] A method for preparing a photocatalyst, comprising the following steps:

[0090] Step S1: Pre-treatment of walnut shell raw materials: Remove mold, sand and gravel impurities from the walnut shells, ultrasonically clean them 3 times with deionized water for 15 minutes each time, and then place them in an oven to dry at 60℃ for 12 hours until constant weight. After preliminary crushing, pass them through a 100-mesh standard sieve to obtain coarse walnut shell powder.

[0091] Step S2, High-energy shear flash extraction activation treatment: The walnut shell powder prepared in step S1 is mixed with a 70% ethanol aqueous solution at a solid-liquid ratio of 1g:30mL. High-energy shear intermittent flash extraction is performed using a flash extractor at a speed of 15000rpm. Each treatment lasts for 30s, with a 20s interval, and the cycle is repeated 3 times to fully break the lignin-cellulose cross-linked structure and expose the phenolic hydroxyl functional groups in the lignin.

[0092] Step S3, Mild Activation Treatment: 100 mL of the flash-extraction modified walnut shell powder solution was added to 15 mL of 3wt% sodium hydroxide solution and 8 mL of 5wt% hydrogen peroxide solution, and the mixture was gently reacted in a 60℃ water bath for 4 hours to achieve mild activation of the phenolic hydroxyl groups into salts. After the reaction, the mixture was filtered, and the filter cake was repeatedly washed with deionized water until the pH of the filtrate reached 6.5 to completely remove free sodium hydroxide. The mixture was then vacuum dried at 60℃ for 8 hours to obtain activated walnut shell powder.

[0093] Step S4, Reverse-phase suspension dispersion and hydrolysis reaction: 3g of activated walnut shell powder was ultrasonically dispersed in 50mL of aqueous solution. Reverse-phase suspension technology was used, with 1g of Tween 80 as surfactant, 250mL of toluene as oil phase, and walnut shell aqueous dispersion as aqueous phase to form a water-in-oil system. After continuous stirring to form a turbid liquid, 1g of tetrabutyl titanate was slowly added dropwise to the system. The titanium source slowly diffused through the oil phase to the surface of the walnut shell particles in the aqueous phase. In-situ hydrolysis reaction was carried out for 12h under stirring at room temperature.

[0094] Step S5, Precursor Post-processing: The reaction product generated in step S4 is centrifuged, washed repeatedly with anhydrous ethanol and deionized water to remove residual solvent and unreacted raw materials, and dried at 60°C for 10 hours to obtain the precursor.

[0095] Step S6, In-situ Calcination Modification under Inert Atmosphere: The precursor is spread evenly in a corundum boat and placed in a tube furnace. Nitrogen gas is introduced at a flow rate of 100 mL / min for 30 minutes to completely purge the air from the furnace. Calcination is then performed using a programmed temperature increase of 5 °C / min, maintaining an inert atmosphere throughout the process. After calcination, the mixture is allowed to cool naturally to room temperature under inert gas protection, then ground to obtain carbon-doped oxygen-rich vacancies. Photocatalyst.

[0096] Example 2

[0097] A method for preparing a photocatalyst, comprising the following steps:

[0098] Step S1: Pre-treatment of walnut shell raw materials: Remove mold, sand and gravel impurities from the walnut shells, ultrasonically clean them 5 times with deionized water for 20 minutes each time, and then place them in an oven to dry at 60℃ for 12 hours until constant weight. After preliminary crushing, pass them through a 100-mesh standard sieve to obtain coarse walnut shell powder.

[0099] Step S2, High-energy shear flash extraction activation treatment: The walnut shell powder prepared in step S1 is mixed with a 70% ethanol aqueous solution at a solid-liquid ratio of 1g:50mL. High-energy shear intermittent flash extraction is performed using a flash extractor at a speed of 15000rpm. Each treatment lasts for 30s, with a 20s interval, and the cycle is repeated 5 times to fully break the lignin-cellulose cross-linked structure and expose the phenolic hydroxyl functional groups in the lignin.

[0100] Step S3, Mild Activation Treatment: Add 100 mL of the flash-extracted modified walnut shell powder solution to 10 mL of 5 wt% sodium hydroxide solution and 5 mL of 8 wt% hydrogen peroxide solution, mix, and react gently in a water bath at 60℃ for 4 h; after the reaction is complete, filter, and repeatedly wash the filter cake with deionized water until the pH of the filtrate is 7.5 to completely remove free sodium hydroxide, and vacuum dry at 80℃ for 12 h to obtain activated walnut shell powder.

[0101] Step S4, Reverse-phase suspension dispersion and hydrolysis reaction: 3g of activated walnut shell powder was ultrasonically dispersed in 50mL of aqueous solution. Reverse-phase suspension technology was used, with 1g of Tween 80 as surfactant, 250mL of toluene as oil phase, and walnut shell aqueous dispersion as aqueous phase to form a water-in-oil system. After continuous stirring to form a turbid liquid, 1g of tetrabutyl titanate was slowly added dropwise to the system. The titanium source slowly diffused through the oil phase to the surface of the walnut shell particles in the aqueous phase. In-situ hydrolysis reaction was carried out for 12h under stirring at room temperature.

[0102] Step S5, Precursor Post-processing: The reaction product generated in step S4 is centrifuged, washed repeatedly with anhydrous ethanol and deionized water to remove residual solvent and unreacted raw materials, and dried at 80°C for 10 hours to obtain the precursor.

[0103] Step S6, In-situ Calcination Modification under Inert Atmosphere: The precursor is spread evenly in a corundum boat and placed in a tube furnace. Nitrogen gas is introduced at a flow rate of 200 mL / min for 30 minutes to completely purge the air from the furnace. Calcination is then performed using a programmed temperature increase of 5 °C / min, maintaining an inert atmosphere throughout the process. After calcination, the mixture is allowed to cool naturally to room temperature under inert gas protection, then ground to obtain carbon-doped oxygen-rich vacancies. Photocatalyst.

[0104] Example 3

[0105] A method for preparing a photocatalyst, comprising the following steps:

[0106] Step S1: Pre-treatment of walnut shell raw materials: Remove mold, sand and gravel impurities from the walnut shells, ultrasonically clean them 5 times with deionized water for 20 minutes each time, and then place them in an oven to dry at 60℃ for 12 hours until constant weight. After preliminary crushing, pass them through a 100-mesh standard sieve to obtain coarse walnut shell powder.

[0107] Step S2, High-energy shear flash extraction activation treatment: The walnut shell powder prepared in step S1 is mixed with 70% ethanol aqueous solution at a solid-liquid ratio of 1g:40mL. High-energy shear intermittent flash extraction is performed using a flash extractor at a speed of 15000rpm. Each treatment lasts 30s, with a 20s interval, and the cycle is repeated 5 times to fully break the lignin-cellulose cross-linked structure and expose the phenolic hydroxyl functional groups in the lignin.

[0108] Step S3, Mild Activation Treatment: Add 100 mL of the flash-extracted modified walnut shell powder solution to 12 mL of 5 wt% sodium hydroxide solution and 6 mL of 8 wt% hydrogen peroxide solution, mix, and react gently in a water bath at 60℃ for 4 h; after the reaction is complete, filter, and repeatedly wash the filter cake with deionized water until the pH of the filtrate is 7.5 to completely remove free sodium hydroxide, and vacuum dry at 80℃ for 12 h to obtain activated walnut shell powder.

[0109] Step S4, Reverse-phase suspension dispersion and hydrolysis reaction: 3g of activated walnut shell powder was ultrasonically dispersed in 50mL of aqueous solution. Reverse-phase suspension technology was used, with 1g of Tween 80 as surfactant, 250mL of toluene as oil phase, and walnut shell aqueous dispersion as aqueous phase to form a water-in-oil system. After continuous stirring to form a turbid liquid, 1g of tetrabutyl titanate was slowly added dropwise to the system. The titanium source slowly diffused through the oil phase to the surface of the walnut shell particles in the aqueous phase. In-situ hydrolysis reaction was carried out for 12h under stirring at room temperature.

[0110] Step S5, Precursor Post-processing: The reaction product generated in step S4 is centrifuged, washed repeatedly with anhydrous ethanol and deionized water to remove residual solvent and unreacted raw materials, and dried at 80°C for 10 hours to obtain the precursor.

[0111] Step S6, In-situ Calcination Modification under Inert Atmosphere: The precursor is spread evenly in a corundum boat and placed in a tube furnace. Nitrogen gas is introduced at a flow rate of 200 mL / min for 30 minutes to completely purge the air from the furnace. Calcination is then performed using a programmed temperature increase of 5 °C / min, maintaining an inert atmosphere throughout the process. After calcination, the mixture is allowed to cool naturally to room temperature under inert gas protection, then ground to obtain carbon-doped oxygen-rich vacancies. Photocatalyst.

[0112] Comparative Example 1 (Unactivated treatment and suspension polymerization control group)

[0113] This comparative example did not undergo unactivated treatment or suspension polymerization treatment; all other steps and parameters were the same as in Example 1, and a TiO2 / C photocatalyst was obtained.

[0114] The photocatalytic degradation performance of the photocatalysts prepared in Example 1 and Comparative Example 1 was tested. The specific test procedure was as follows:

[0115] A tetracycline hydrochloride aqueous solution with an initial concentration of 20 mg / L was prepared as the target degradation system;

[0116] Add 10 mg of catalyst to 50 mL of tetracycline hydrochloride solution, stir in the dark for 30 min, and reach adsorption-desorption equilibrium;

[0117] A 300W xenon lamp with a 420nm cutoff filter was used to simulate visible light. The light was turned on, and 3mL samples were taken at regular intervals. The samples were filtered through a 0.22μm filter membrane, and the absorbance was measured at the characteristic wavelength of 320nm using a UV-Vis spectrophotometer. The degradation rate of tetracycline hydrochloride was then calculated.

[0118] To verify the active species generation capacity, light absorption characteristics, and degradation performance of the photocatalyst prepared in this invention, examples 1-3 were used. Of the samples, Example 1, which showed the best performance in the preliminary test, was selected. Sample and Comparative Example 1 were prepared The sample underwent a series of tests. The results are as follows: Figure 3-5 As shown. Figure 3 As shown, electron paramagnetic resonance (ESR) spectroscopy tests using DMPO trapping agent indicate that Example 1... The photocatalyst exhibited a characteristic quartet signal with extremely high intensity after 2 minutes of visible light irradiation. Figure 3 a), while comparative example 1 The signal strength is significantly weaker and accompanied by more noise under the same conditions. Figure 3 (b) Neither showed a significant signal under dark conditions. This data directly demonstrates that the oxygen-rich vacancy structure constructed by the method of this invention can effectively capture photogenerated electrons and transfer them to adsorbed oxygen molecules, thereby significantly promoting superoxide radical activity. The efficient generation of these organisms verifies the core mechanism of oxygen vacancy-mediated selective generation of bioactive species.

[0119] Figure 4 shows the UV-Vis diffuse reflectance absorption spectra of the two samples. It can be seen that the sample prepared in Example 1... The photocatalyst exhibited significantly higher light absorption intensity across the entire test wavelength range compared to Comparative Example 1, with a noticeable redshift at the absorption edge extending into the visible light region. This enhanced photoresponse capability is attributed to the successful doping of carbon atoms derived from walnut shells. The introduction of lattice and oxygen vacancy defect energy levels synergistically narrows the bandgap of the material, enhancing the catalyst's ability to capture visible light photons.

[0120] Figure 5 further illustrates the degradation kinetics of tetracycline hydrochloride by the two photocatalysts under visible light irradiation. Experimental results show that the degradation kinetics of tetracycline hydrochloride in Example 1... The photocatalyst exhibited a significantly higher degradation rate for tetracycline hydrochloride than Comparative Example 1. As the reaction time increases, the concentration ratio of pollutants in the reaction system of Example 1 decreases ( The degradation rate was more rapid, dropping below 0.2 after 20 minutes, while Comparative Example 1 only dropped to around 0.4. This superior degradation performance stems from the enhanced light absorption capacity and improved superoxide radical generation efficiency, indicating that the carbon doping and oxygen vacancy synergistic modification achieved through the "one source, multiple energy" strategy of walnut shells in this invention effectively solves the problems of traditional... The problem of low visible light utilization and insufficient generation of active species has been solved, achieving efficient removal of tetracycline hydrochloride.

[0121] The embodiments of the present invention have been described in detail above. However, the present invention is not limited to the above embodiments. Within the scope of knowledge possessed by those skilled in the art, various changes can be made without departing from the spirit of the present invention.

Claims

1. A method for preparing a photocatalyst, characterized in that: Follow these steps: Step S1: Pre-treatment of walnut shell raw materials: Remove mold, sand and gravel impurities from the walnut shells, ultrasonically clean them with deionized water 3-5 times, 15-20 minutes each time, and then place them in an oven to dry at 60℃ for 12 hours until constant weight. After preliminary crushing, pass them through a 100-mesh standard sieve to obtain coarse walnut shell powder. Step S2, High-energy shear flash extraction and activation treatment: The coarse walnut shell powder prepared in step S1 was mixed with a 70% volume fraction ethanol aqueous solution and subjected to high-energy shear intermittent flash extraction using a flash extractor at a speed of 15000 rpm. Each treatment lasted 30 seconds, with a 20-second interval, and the process was repeated 3-5 times. Step S3, Gentle Activation Treatment: The modified walnut shell powder solution was added to sodium hydroxide solution and hydrogen peroxide solution, and reacted gently in a water bath at 60℃ for 4 hours. After the reaction, the solution was filtered, and the filter cake was repeatedly washed with deionized water until the pH of the filtrate was 6.5~7.5 to completely remove free sodium hydroxide. The solution was then vacuum dried at 60-80℃ for 8-12 hours to obtain activated walnut shell powder. Step S4, reverse-phase suspension dispersion and hydrolysis reaction: 3g of activated walnut shell powder was ultrasonically dispersed in 50mL of aqueous solution. Using reverse-phase suspension technology, 1g of Tween 80 was used as a surfactant, 250mL of toluene was used as the oil phase, and the walnut shell aqueous dispersion was used as the aqueous phase to form a water-in-oil system. After continuous stirring to form a turbid liquid, 1g of tetrabutyl titanate was slowly added dropwise to the system. The titanium source slowly diffused through the oil phase to the surface of the walnut shell particles in the aqueous phase. The in-situ hydrolysis reaction was carried out for 12h under stirring at room temperature. Step S5, Precursor Post-processing: Centrifuge the reaction product generated in step S4, wash it repeatedly with anhydrous ethanol and deionized water to remove residual solvent and unreacted raw materials, and dry it at 60-80℃ for 10h to obtain the precursor. Step S6: In-situ calcination modification under inert atmosphere: The precursor was spread evenly in a corundum ark and placed in a tubular atmosphere furnace. Nitrogen gas was introduced at a flow rate of 100-200 mL / min for 30 minutes to completely purge the air from the furnace. Calcination was then performed using a programmed temperature increase of 5 °C / min, maintaining an inert atmosphere throughout the process. After calcination, the furnace was allowed to cool naturally to room temperature under inert gas protection and then ground to obtain carbon-doped oxygen-rich vacancies. Photocatalyst.

2. The method for preparing a photocatalyst according to claim 1, characterized in that: In step S2, the solid-liquid ratio of coarse walnut shell powder to ethanol aqueous solution is 1g:30mL-50mL.

3. The method for preparing a photocatalyst according to claim 2, characterized in that: In step S3, the concentration of sodium hydroxide solution is 3-5 wt%, and the volume ratio of walnut shell powder solution to sodium hydroxide solution is 100 ml: 10-15 ml.

4. The method for preparing a photocatalyst according to claim 3, characterized in that: The concentration of the hydrogen peroxide solution in step S3 is 5-8 wt%, and the volume ratio of walnut shell powder solution to hydrogen peroxide is 100 ml: 5-8 mL.

5. The method for preparing a photocatalyst according to claim 4, characterized in that: Follow these steps: Step S1: Pre-treatment of walnut shell raw materials: Remove mold, sand and gravel impurities from the walnut shells, ultrasonically clean them three times with deionized water for 15 minutes each time, and then place them in an oven to dry at 60°C for 12 hours until constant weight. After preliminary crushing, pass them through a 100-mesh standard sieve to obtain coarse walnut shell powder. Step S2, High-energy shear flash extraction and activation treatment: The coarse walnut shell powder prepared in step S1 was mixed with a 70% ethanol aqueous solution at a solid-liquid ratio of 1g:30mL. The mixture was subjected to high-energy shear intermittent flash extraction using a flash extractor at a speed of 15000rpm. Each treatment lasted 30s, with a 20s interval, and the process was repeated 3 times. Step S3, Gentle Activation Treatment: 100 mL of the flash-extraction modified walnut shell powder solution was added to 15 mL of 3 wt% sodium hydroxide solution and 8 mL of 5 wt% hydrogen peroxide solution, and the mixture was gently reacted in a water bath at 60℃ for 4 h. After the reaction was completed, the mixture was filtered, and the filter cake was repeatedly washed with deionized water until the pH of the filtrate was 6.5 to completely remove free sodium hydroxide. The mixture was then vacuum dried at 60℃ for 8 h to obtain activated walnut shell powder. Step S4, reverse-phase suspension dispersion and hydrolysis reaction: 3g of activated walnut shell powder was ultrasonically dispersed in 50mL of aqueous solution. Using reverse-phase suspension technology, 1g of Tween 80 was used as a surfactant, 250mL of toluene was used as the oil phase, and the walnut shell aqueous dispersion was used as the aqueous phase to form a water-in-oil system. After continuous stirring to form a turbid liquid, 1g of tetrabutyl titanate was slowly added dropwise to the system. The titanium source slowly diffused through the oil phase to the surface of the walnut shell particles in the aqueous phase. The in-situ hydrolysis reaction was carried out for 12h under stirring at room temperature. Step S5, Precursor Post-processing: The reaction product generated in step S4 was centrifuged, washed repeatedly with anhydrous ethanol and deionized water to remove residual solvent and unreacted raw materials, and dried at 60°C for 10 hours to obtain the precursor. Step S6: In-situ calcination modification under inert atmosphere: The precursor was spread evenly in a corundum ark and placed in a tube furnace. Nitrogen gas was introduced at a flow rate of 100 mL / min for 30 minutes to completely purge the air from the furnace. Calcination was then performed using a programmed temperature increase of 5 °C / min, maintaining an inert atmosphere throughout the process. After calcination, the mixture was allowed to cool naturally to room temperature under inert gas protection and then ground to obtain carbon-doped oxygen-rich vacancies. Photocatalyst.

6. The method for preparing a photocatalyst according to claim 4, characterized in that: Follow these steps: Step S1: Pre-treatment of walnut shell raw materials: Remove mold, sand and gravel impurities from the walnut shells, ultrasonically clean them 5 times with deionized water for 20 minutes each time, and then place them in an oven to dry at 60℃ for 12 hours until constant weight. After preliminary crushing, pass them through a 100-mesh standard sieve to obtain coarse walnut shell powder. Step S2, High-energy shear flash extraction and activation treatment: The coarse walnut shell powder prepared in step S1 was mixed with a 70% ethanol aqueous solution at a solid-liquid ratio of 1g:50mL. The mixture was subjected to high-energy shear intermittent flash extraction using a flash extractor at a speed of 15000rpm. Each treatment lasted 30s, with a 20s interval, and the process was repeated 5 times. Step S3, Gentle Activation Treatment: 100 mL of the flash-extraction modified walnut shell powder solution was added to 10 mL of 5 wt% sodium hydroxide solution and 5 mL of 8 wt% hydrogen peroxide solution, and the mixture was gently reacted in a water bath at 60℃ for 4 h. After the reaction was completed, the mixture was filtered, and the filter cake was repeatedly washed with deionized water until the pH of the filtrate was 7.5 to completely remove free sodium hydroxide. The mixture was then vacuum dried at 80℃ for 12 h to obtain activated walnut shell powder. Step S4, reverse-phase suspension dispersion and hydrolysis reaction: 3g of activated walnut shell powder was ultrasonically dispersed in 50mL of aqueous solution. Using reverse-phase suspension technology, 1g of Tween 80 was used as a surfactant, 250mL of toluene was used as the oil phase, and the walnut shell aqueous dispersion was used as the aqueous phase to form a water-in-oil system. After continuous stirring to form a turbid liquid, 1g of tetrabutyl titanate was slowly added dropwise to the system. The titanium source slowly diffused through the oil phase to the surface of the walnut shell particles in the aqueous phase. The in-situ hydrolysis reaction was carried out for 12h under stirring at room temperature. Step S5, Precursor Post-processing: The reaction product generated in step S4 was centrifuged, washed repeatedly with anhydrous ethanol and deionized water to remove residual solvent and unreacted raw materials, and dried at 80°C for 10 hours to obtain the precursor. Step S6: In-situ calcination modification under inert atmosphere: The precursor was spread evenly in a corundum ark and placed in a tube furnace. Nitrogen gas was introduced at a flow rate of 200 mL / min for 30 minutes to completely purge the air from the furnace. Calcination was then performed using a programmed temperature increase of 5 °C / min, maintaining an inert atmosphere throughout the process. After calcination, the mixture was allowed to cool naturally to room temperature under inert gas protection, and then ground to obtain carbon-doped oxygen-rich vacancies. Photocatalyst.

7. The application of a photocatalyst in the degradation of tetracycline hydrochloride, characterized in that: Carbon-doped oxygen-rich vacancies prepared by the method for preparing a photocatalyst according to any one of claims 1-6 Photocatalyst, The photocatalyst was added to the tetracycline hydrochloride solution and stirred in the dark for 25-35 minutes to reach adsorption-desorption equilibrium. Then, the tetracycline hydrochloride was degraded by irradiation with visible light.

8. The application of the photocatalyst according to claim 7 in the degradation of tetracycline hydrochloride, characterized in that: The After the photocatalyst has degraded, it is centrifuged and recovered, washed 3-5 times with deionized water and ethanol, and then dried for reuse.

Citation Information

Patent Citations

  • Method for preparing carbon-doped titanium dioxide composite material and application thereof

    CN102205236A

  • Titanium dioxide supported type composite carbon aerogel as well as preparation and application thereof

    CN108816259A